Tourism and insecurity in the world - Simplice Asongu; Joseph I. Uduji; Elda N. Okolo-Obasi (African Governance and Development Institute (AGDI), 2019)
The study assesses the role of forces of law and order in modulating the insecurity-tourism nexus in 163 countries for the period 2010 to 2015. Policy syndromes or insecurity dynamics include: violent crime, access to weapons, political instability and perception of criminality while the policy variables of forces of law and order are captured with "security officers & police" and "armed service personnel". The empirical evidence is based on Negative Binomial regressions. The findings show that the policy variables can be effectively used to crowd-out the negative incidence of policy syndromes on tourist arrivals. The results are contingent on net effects (from conditional and unconditional effects), insecurity dynamics and thresholds. A threshold is an inflexion point at which the unfavorable unconditional effect from a policy syndrome of insecurity on tourist arrivals is completely neutralized by policy variables of forces of law and order. Policy implications are discussed.
Keywords: D74; Z32; Z38; 330; Insecurity; Peace; Tourism